Association of Cognitive Impairment With Treatment and Outcomes in Older Myocardial Infarction Patients: A Report From the NCDR Chest Pain–MI Registry - Bagai, Akshay; Chen, Anita Y.; Udell, Jacob A.; Dodson, John A.; McManus, David D.; Maurer, Mathew S.; Enriquez, Jonathan R.; Hochman, Judith; Goyal, Abhinav; Henry, Timothy D.; Gulati, Martha; Garratt, Kirk N.; et al. (Journal of the American Heart Association, 2019)
Background Little is known regarding use of cardiac therapies and clinical outcomes among older myocardial infarction (MI) patients with cognitive impairment. Methods and Results Patients ≥65 years old with MI in the NCDR (National Cardiovascular Data Registry) Chest Pain-MI Registry between January 2015 and December 2016 were categorized by presence and degree of chart-documented cognitive impairment. We evaluated whether cognitive impairment was associated with all-cause in-hospital mortality after adjusting for known prognosticators. Among 43 812 ST-segment-elevation myocardial infarction (STEMI) patients, 3.9% had mild and 2.0% had moderate/severe cognitive impairment; among 90 904 non-ST-segment-elevation myocardial infarction (NSTEMI patients, 5.7% had mild and 2.6% had moderate/severe cognitive impairment. A statistically significant but numerically small difference in the use of primary percutaneous coronary intervention was observed between patients with STEMI with and without cognitive impairment (none, 92.1% versus mild, 92.8% versus moderate/severe, 90.4%; P=0.03); use of fibrinolysis was lower among patients with cognitive impairment (none, 40.9% versus mild, 27.4% versus moderate/severe, 24.2%; P<0.001). Compared with NSTEMI patients without cognitive impairment, rates of angiography, percutaneous coronary intervention, and coronary artery bypass grafting were significantly lower among patients with NSTEMI with mild (41%, 45%, and 70% lower, respectively) and moderate/severe cognitive impairment (71%, 74%, and 93% lower, respectively). After adjustment, compared with no cognitive impairment, presence of moderate/severe (STEMI: odds ratio, 2.2, 95% CI, 1.8-2.7; NSTEMI: odds ratio, 1.7, 95% CI, 1.4-2.0) and mild cognitive impairment (STEMI: OR, 1.3, 95% CI, 1.1-1.5; NSTEMI: odds ratio, 1.3, 95% CI, 1.2-1.5) was associated with higher in-hospital mortality. Conclusions Patients with NSTEMI with cognitive impairment are substantially less likely to receive invasive cardiac care, while patients with STEMI with cognitive impairment receive similar primary percutaneous coronary intervention but less fibrinolysis. Presence and degree of cognitive impairment was independently associated with increased in-hospital mortality. Approaching clinical decision making for older patients with MI with cognitive impairment requires further study.